1998
DOI: 10.1210/jc.83.9.3225
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Placental Production of Leptin in Preeclampsia: Possible Involvement of Placental Hypoxia

Abstract: Preeclampsia (PE) is a hypertensive disorder, which develops in late pregnancy and is usually associated with placental hypoxia and dysfunction. We have recently demonstrated that leptin is a novel placenta-derived hormone in humans and suggested its significance in human pregnancy (see Ref. 19). To explore the changes in the leptin production in placenta in PE, we measured the plasma leptin level and placental leptin messenger RNA expression in pregnant women with PE. Plasma leptin levels in preeclamptic wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

22
186
2
10

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(221 citation statements)
references
References 0 publications
22
186
2
10
Order By: Relevance
“…Our data are in agreement with the findings of another study [14] which showed that hypoxia increases placental leptin production. That study found that in vitro a rise in leptin production in placental cells did not take place until after 72 h of hypoxia [14].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our data are in agreement with the findings of another study [14] which showed that hypoxia increases placental leptin production. That study found that in vitro a rise in leptin production in placental cells did not take place until after 72 h of hypoxia [14].…”
Section: Discussionsupporting
confidence: 93%
“…That study found that in vitro a rise in leptin production in placental cells did not take place until after 72 h of hypoxia [14]. Because during hypoxic conditions a significant increase in fetal EPO concentrations can be observed within 2 to 4 h [16], the increased cord plasma leptin, together with the increased EPO concentrations in both amniotic fluid and cord plasma, probably reflect chronic or subchronic rather than acute fetoplacental hypoxia.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…28 Placental leptin production is elevated under hypoxic conditions, 29 and leptin levels in PE are significantly higher than in normal pregnancies, [30][31][32] suggesting that leptin derived from the placenta may play a role in the pathophysiology of PE through insulin resistance, autonomic activation or direct effects on the endothelium. Next, we investigated whether there were significant differences in adipocytokines in women with early-and late-onset PE and in healthy pregnant women.…”
Section: Discussionmentioning
confidence: 99%